A systematic review on the effectiveness of thermography in diagnosis of diseases. Issue 2 (21st May 2013) - Sajjadi, Haniyeh Sadate; Seyedin, Hesam; Aryankhesal, Aidin; Asiabar, Ali Sarabi
ABSTRACT Collecting and analyzing appropriate information and performing comprehensive systematic studies, considering safety, effectiveness, and cost effectiveness of the technologies are prerequisites for making decisions on buying and using different diagnostic and therapeutic equipment. This study aimed to systematically identify and analyze available evidences related to the effectiveness of contact thermography technique in diagnosis of different diseases. This study was a systematic review of published and gray literature. We searched relevant databases, bibliography of related papers, and companies' websites, using appropriate search strategies and key words. The CASP tool was used by two experts to evaluate the quality of retrieved papers and inconsistencies were resolved by discussion. After removal of duplicate citations, 308 titles were identified through database searching, among which 276 were excluded on reviewing of the titles and abstracts. The full texts of the remaining papers (32) were assessed against the inclusion criteria and 14 papers were recognized qualified, which were categorized into three groups of: breast cancer, DVT, and others. The results showed although contact thermography is a safe, rapid and cheap technique to be used in screening and diagnosing different diseases, but results did not show any acceptable diagnostic value in comparison to other diagnostic techniques. It might be beneficial to use it as a complementary technique. More research is recommended in this area. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 188–193, 2013